2000
DOI: 10.15760/etd.1842
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Capability Maturity Models and Relevant Practices as Solutions Addressing IT Service Offshoring Project Issues

Abstract: Chi-square test was applied to test all the hypotheses using p= 0.05 as the critical significance level: H1: The relationship between adopting CMM/CMMI industrial standards and the IT offshoring issues. H2: The relationship between CMM/CMMI industrial standards Maturity level achieved and the frequency of issues experienced. H3: The relationship between MM/CMMI industrial standards practices and the frequency of issues experienced. H4.1: The relationship between adopting CMMM/CMMI industrial standards and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 207 publications
1
4
0
Order By: Relevance
“…Additionally, this response rate is consistent with the response rate of a typical PhD dissertation survey in the field of engineering and technology management, which typically obtains a response rate range from 6.1% to 11.4% [252,257,224]. Therefore, the response rate in this dissertation of 12.8 percent is well within the expected and acceptable range.…”
Section: Response Ratesupporting
confidence: 81%
See 1 more Smart Citation
“…Additionally, this response rate is consistent with the response rate of a typical PhD dissertation survey in the field of engineering and technology management, which typically obtains a response rate range from 6.1% to 11.4% [252,257,224]. Therefore, the response rate in this dissertation of 12.8 percent is well within the expected and acceptable range.…”
Section: Response Ratesupporting
confidence: 81%
“…In a number of previous desertions the acceptable score is 4 -Somewhat Closely for relevance and 4-Somewhat Easy for ease of answering questions [219,224]. Accordingly, after incorporating experts' feedback, the goal in this dissertation is to have all surrey questions score above 4 -Somewhat Closely for relevance and 4-Somewhat Easy for ease of answering questions.…”
Section: Appendix E)mentioning
confidence: 99%
“…This makes the lecture difficult to design and execute since it implies that the teacher has to select a subset of the KAs to cover in a short time budget, and it also supposes that the teacher is expert in all the KAs which, of course, can rarely be the case; (b) Most of the KA subtopics are covered thanks to Engineering Projects offered in the curriculum. Engineering Economics (12) and Software Quality (29) and, more surprisingly, Software Maintenance (5). This last fact seems in direct opposition with the reality of engineering activities which, for the majority, consists in supporting software evolution and maintenance.…”
Section: Ka Name Mean Minmentioning
confidence: 99%
“…It is thus interesting to observe industry practice through the capability maturity model in order to better determine the problem of improving software engineering practice. According to available studies [15,[27][28][29], which we have witnessed during our own empirical experience in handling more than 600 internships in industry for bachelor and master students and as expert for the court of justice on conformance questions in trials for the software industry, we can state that: (a) Approximately 3/4 of companies are at level 1 or 2 (initial or repeatable); (b) Among the companies that go for CMMI appraisal, approximately 80% are at or below level 3 (defined) and 20% at level 4 (managed) and 5 (optimizing).…”
mentioning
confidence: 99%
“…According to Mckeen and Smith (2009), in the early 2000s, organisations started to realise that they can meet strategic objectives, drive costs down and add capacity by turning to outsourcing. Salman (2014) defined IT outsourcing as 'the turning over of a firm's computer operations, network operations, software development and maintenance or other IT functions or services to a provider for a specified time'. Gorla and Somers (2014) suggested that IS outsourcing annual growth rate is at 14% with the current IT services market value at $746 billion.…”
Section: Literature Reviewmentioning
confidence: 99%